The Role of Maxim and Implicature in “Jurassic World” Movie: Pragmatic Approach - Simaremare, Alvano Padrepio; Handayani, Nurma Dhona (PROJECT (Professional Journal of English Education), 2026)
This study analyzes conversational implicature and the flouting of Gricean maxims in the movie “Jurassic World” using a qualitative descriptive method. The data consist of selected utterances spoken by the main characters, such as Owen Grady, Claire Dearing, and other supporting characters, which were transcribed and analyzed based on Grice's (1975) cooperative principle, including the maxims of quantity, quality, relation, and manner. The findings show that the characters frequently flout these maxims to express hidden meanings, especially in moments of conflict, persuasion, and moral tension arising from human control and manipulation of nature. Such flouting is not a communication failure, but rather a pragmatic strategy to assert dominance, conceal fear, or negotiate power. The study concludes that conversational implicature and maxim flouting in “Jurassic World” reflect realistic and strategic human communication under pressure and uncertainty. This research also highlights the relevance of pragmatic theory in analyzing film dialogues as a medium of complex social and emotional expression.